Heterogeneous Nucleation and Growth of Barium Sulfate at Organic–Water Interfaces: Interplay between Surface Hydrophobicity and Ba2+ Adsorption - Chong Dai; Andrew G. Stack; Koishi, Ayumi; Fernandez-Martinez, Alejandro; Lee, Sang Soo; Yandi* Hu (Langmuir, 2016)
{ Barium sulfate (BaSO4) is a common scale-forming mineral in natural and engineered systems, yet the rates and mechanisms of heterogeneous BaSO4 nucleation are not understood. To address these, we created idealized interfaces on which to study heterogeneous nucleation rates and mechanisms, which also are good models for organic–water interfaces: self-assembled thin films terminated with different functional groups (i.e., −COOH, −SH, or mixed −SH & COOH) coated on glass slides. BaSO4 precipitation on coatings from Barite-supersaturated solutions (saturation index